Rancang Bangun Sistem Informasi Inventory Barang Berbasis Web Menggunakan Metode RAD (Studi Kasus: CV. Baja Karya Abadi) - Giri Nikmatullah, Alexs; Zaida Muflih, Ghufron (Jurnal Manajemen Informatika & Teknologi, 2026)
CV. Baja Karya Abadi, a steel and iron distribution company, still manages its inventory manually using notebooks. This has resulted in stock data inaccuracies (15–20% discrepancies over the past six months), recording errors, vulnerability to document loss, and slow reporting. This research aims to design, build, and evaluate a web-based inventory information system integrated with the Rapid Application Development (RAD) method. RAD was chosen for its flexibility, speed, and active user involvement. The system was developed using the CodeIgniter 4 framework and MySQL database, encompassing multi-level login modules (admin, owner, cashier), a summary dashboard with charts, item/supplier data management, sales/purchase transactions, supplier debt recording, due date reminders, and reporting. System testing was conducted using Black Box Testing with Boundary Value Analysis (BVA) and User Acceptance Testing (UAT). The BVA results showed that all functions operated as required. UAT involving 5 respondents (owner, warehouse staff, financial staff) yielded an average score of 4.36 out of 5 (87.2%), categorized as “Very Good”. This system has proven to improve recording efficiency, stock accuracy, reporting speed, and assists in debt management and supplier payment due date tracking.